Carbothermal reduction of iron and silicon oxides in ironstone ore. (2nd April 2016) - Maroufi, S.; Ciezki, G.; Jahanshahi, S.; Ostrovski, O.
Abstract : The paper examines carbothermal reduction of iron and silicon oxides in ironstone ore which can be a valuable source of iron and silicon in production of ferrosilicon and silicomanganese. The original ore was provided as a crushed ore and a lumpy ore. Crushed ironstone ore contained higher Fe2 O3 concentration (40.6 wt-%) and lower SiO2 content (44.3 wt-%) compared to the lumpy one (21.2 wt-% Fe2 O3, 68.9 wt-% SiO2 ); phases detected by XRD and SEM/EDS analyses included haematite and quartz. Reduction of ironstone ores by graphite was examined at the temperature range 1400–1600°C in CO atmosphere. XRD analysis of both ironstone ores reduced at 1400°C identified the presence of quartz, cristobalite and metallic iron. Reduction of iron oxides was close to completion at 1400°C; with increasing temperature to 1500°C, Fe3 Si was formed. Quartz and cristobalite were also present in the reduced sample, while no Fe was detected by both XRD and SEM/EDS analyses of samples reduced at 1500°C. The crushed ore reduced at 1600°C, contained Fe5 Si3, Fe3 Si, Fe2 Si, SiC and cristobalite; the same phases except Fe5 Si3 were also identified in the lumpy ore reduced at this temperature. Extent of silica reduction increased with increasing temperature. Equilibrium phases in carbothermal reduction of ironstone ores were analysed using CSIRO's Multiphase Equilibrium model. In general, calculated results were consistent with experimental data, although equilibrium was not fully reached under experimental conditions of this study.